Development of a diet quality index and assessment of its reliability and validity among students at a Malaysian public university - Fokeena, Waqia Begum (2016)
Despite that university students are at risk of having a poor diet quality, there is no reliable and valid instrument to measure the diet quality of Malaysian university students. The objectives of this study were to develop and validate a diet quality index among a sample of university students, to assess their diet quality and to determine its relation to physical activity level and socio-demographic factors. The Malaysian Dietary Guidelines and Malaysian Food Pyramid were used in the formulation of a 12-item diet quality index. A cross-sectional study was conducted among 320 students at a Malaysian public university. Data collected through face-toface interview was used to determine the internal consistency reliability, construct validity, concurrent validity and validity with relation to body weight status of the index. Test-retest reliability was measured among 31 students from the sample. A Cronbach’s alpha value of 0.780, mean inter-item correlation of 0.353 and corrected-item total correlation above 0.3 were found after five items were deleted from the index. The intra-class correlation for test-retest reliability was above 0.7. Principal component analysis revealed the presence of four components with eigenvalues exceeding 1. Only one component explaining 41.7% of variance was retained. With consideration to the outcomes of internal consistency and construct validity, the 7-item diet quality index consisting of Wholegrain cereals, Fruits, Vegetables, Fish, Fat-rich foods, Salt-rich foods and Sugar-rich foods was used to address the other study objectives. The mean total diet quality score of participants was 18.7±3.42. Diet quality scores showed significant negative correlation with sugar intake, and significant positive correlation with intakes of fibre and nine micronutrients. The correlation coefficients were less than 0.3 and ranged from 0.128 to 0.242. Diet quality scores did not significantly correlate with body weight status. Using a cut-off value of 16.5, the proportion of participants at risk of poor diet quality and at lower risk of poor diet quality were 23.1% and 76.9% respectively. Overall, above 80% of participants did not meet the dietary guidelines for wholegrain cereals, fruits, vegetables and fish. Significant differences in dietary guideline adherence were observed for fish, fat-rich foods, salt-rich foods and sugar-rich foods and students at lower risk of poor diet quality showed better adherence. Among the socio-demographic factors, only gender was significantly associated with diet quality scores (p=0.006). Females had higher diet quality scores as compared to males. There was no significant correlation between diet quality scores and physical activity level. The 7-item diet quality index is a valid and reliable instrument to measure diet quality of students at the selected Malaysian public university. Nevertheless, caution need to be taken when using the index to evaluate diet quality as several important food groups do not form part of it. Students in general require improvement in their diet with respect to wholegrain cereals, fruits, vegetables and fish. Excessive intake of fat, salt and sugar and inadequate intake of fish may place students at risk of poor diet quality. Males require more focus than females as they may be at greater risk of poor diet quality.